Prevalence and determinants of Chlamydia trachomatis infection among sexually active women in Turin, Italy (Italian Journal of Public Health, 2011)
Background: According to the World Health Organisation, Chlamydia trachomatis (Ct) is the most commonsexually transmitted bacterial agent worldwide.The aim of the present study was to determine the prevalence and risk factors for genital infection with Ctamong sexually active women (14-60 years of age), in Turin (northern Italy).Methods: A cross-sectional study was performed between January 2002 and December 2007 among sexuallyactive women in Turin. All women were tested for Ct infection using the Amplified Ct Assay (Gen-Probe) onan endocervical specimen. The prevalence was calculated as the proportion of Ct-positive women out of thetotal study population. Associations between Ct infection and risk factors (socio-demographic, behavioural,and clinical-gynaecological) were analyzed using the Chi-square test. The level of significance was set at0.05. Risk factors independently associated with Ct infection were determined using a multivariate logisticregression model. The statistical analyses were performed using SPSS (version 17.0).Results: The study included 25,289 women, of whom 1.8% were found to have Ct infection. The prevalenceof Ct infection increased significantly from 1.5% in 2002 to 2.2% in 2007 (χ2 =5.6; p-value
Keywords: Chlamydia trachomatis; prevalence; risk factors; sexually active women